High-fidelity simulation training for improving nursing professional values acquisition - Arrogante, Oscar; Ortuño-Soriano, Ismael; Fernandes-Ribeiro, Ana Sofia; Raurell-Torredà, Marta; Jiménez-Rodríguez, Diana; Zaragoza-García, Ignacio (Nursing ethics, 2025)
Background Nursing professional values form the basis of nursing interventions and serve as a guide for professional practice, reflecting in all interactions with patients and other healthcare professionals. As nursing professional values constitute powerful influencers in nursing practice, a strong commitment to these values is essential for nursing students to provide high-quality care. Aim To evaluate the impact of high-fidelity simulation training on first-year nursing students’ nursing professional values acquisition. Research design Quasi-experimental study using a longitudinal design with a single group pre- and post-intervention evaluation. Participants and research context 202 first-year nursing students at the Complutense University of Madrid (Spain) participated in the study between September 2023 and May 2024. Their nursing professional values were compared at baseline and after the simulation experience using the “Nurses Professional Values Scale-Revised” (NVPS-R). The acquisition of these values was also evaluated using a verification list during simulation sessions. Five simulated scenarios recreated ethics dilemmas, where students should manage conflictive situations with a standardized patient. Ethical considerations The study was approved by the Research Ethics Committee from the Complutense University of Madrid (reference code: CE_20231116_18_SAL). Results Most of the students (84.87%) acquired the nursing professional values needed to manage adequately simulated ethical dilemmas. Nursing students significantly improved their nursing professional values after the simulation sessions. The effect size was medium for the “professional expertise” and “professional mastery” dimensions, and the total score of NVPS-R, whereas the obtained effect size was small for the “ethics” dimension. Conclusion High-fidelity simulation training using standardized patients allows first-year nursing students to acquire and improve nursing professional values. The inclusion of simulation training programs in nursing study plans to foster nursing professional values is needed to train undergraduate nursing students, providing them with the necessary ethical concepts and principles for their future clinical practice and ensuring high-quality care.